Visuomotor Control in Continuous Response Time Tasks across Different Age Groups. Issue 1 (August 2014) - Liu, Guanmin; Chen, David D.; Qin, Chunbo; Chan, John S. Y.; Peng, Kaiping; Yan, Jin H.
The goal was to examine whether visuomotor control and choice response time shared age-related developmental trajectories, and if prior computer experience played an important role in control processes. Children (6–7, 8–9, 10–11 yr.), younger adults (24 yr.) and older adults (76 yr.) performed the cursor pointing and choice response time (CRT) tasks with a computer mouse. Participants moved the mouse cursor back and forth to click two targets on the screen as fast and accurately as possible. In the CRT, based on visual stimuli, participants moved and clicked one of the three targets on the screen as fast and accurately as possible; the time between stimulus onset and clicking the correct target was recorded as the choice response time. Visuomotor performance increased with age to younger adulthood but was worse in the older adult group. CRT performance was also positively related to age among the groups of children, with scores leveling off in the young adult group. Computer experience was statistically significantly related only to visuomotor control, but not to CRT. Optimal CRT performance required only sub-optimal visuomotor control. Cognitive and sensory age declines may be related to the poorer CRT performance in the oldest age group.